EFA Analysis of Factors Affecting the Success of Online Learning in Elementary Schools: An Exploratory Study in Elementary Schools with an International Curriculum - M. Habibi; Nurfaijah Nurfaijah (STAI Hubbulwathan Duri, 2026)
This study was motivated by the numerous variables influencing the success of online learning in elementary schools and the need to identify the most significant underlying factors. A quantitative design employing Exploratory Factor Analysis (EFA) was used. Data were collected from 108 teachers across four elementary schools (SD Islam Al Azhar 32 Padang, SD Telkom, Yari International School, and SafaMarywa Islamic International School). Initially, 23 variables were identified through a teacher opinion survey; however, validity testing retained 20 variables. Sampling adequacy was confirmed (KMO = 0.819), and Bartlett’s test of sphericity was significant (p = 0.001), indicating suitability for factor analysis. The analysis extracted eight principal factors based on eigenvalues and rotated component matrices: (1) Psychological Readiness and Self-Regulation (3.152), (2) Support for Digital Learning Technology (2.264), (3) Teachers’ Pedagogical and Professional Competence (1.663), (4) Quality of Learning Design and Materials (1.426), (5) Teachers’ Instructional Communication (1.313), (6) Supportive Home Learning Environment (1.303), (7) Technological Capabilities of Teachers and Students (1.054), and (8) Students’ Social and Academic Participation (1.030). These findings highlight that successful online learning in elementary education is multifactorial, integrating psychological, technological, pedagogical, and environmental dimensions. The identified factors provide a structured framework for educators to enhance online learning effectiveness and improve student outcomes.